The Spill-Over Of Work–Family Conflict On Career Satisfaction: The Role Of Cynicism And The Boundary Condition Of Organizational Cohesion - Trirahayu, Dewi (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Purpose – This study aims to examine how and when work–family conflict (WFC) affects career satisfaction, both directly and indirectly through cynicism, as well as the moderating role of organizational cohesion as a boundary condition. Design/methodology/approach – Data were collected via a questionnaire survey, yielding 404 valid responses. The research model was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings – The findings confirm that WFC positively influences cynicism and negatively affects career satisfaction. Cynicism was found to have a negative relationship with career satisfaction and to mediate the link between WFC and career satisfaction. Furthermore, organizational cohesion served as an effective buffer, weakening the positive effect of WFC on cynicism and mitigating the negative indirect effect of WFC on career satisfaction. Originality/value – This study contributes to organizational behavior by identifying cynicism as a key mechanism through which WFC reduces career satisfaction. It also shows that organizational cohesion can mitigate the negative effects of WFC, particularly in supportive environments. Practical implications – Human resource practitioners should recognize work–family conflict as a strategic threat that can foster cynicism and ultimately diminish employees' career satisfaction. Keywords – Work–family conflict, Career satisfaction, Cynicism, Organizational cohesion, Social exchange theory